Methyl 3-(3-benzoylthioureido)propanoate - Ibrahim N. Hassan; Chong Yan Yi; Mohammad B. Kassim (Acta Crystallographica Section E, 2011)
In the title compound, C12H14N2O3S, the propyl acetate group and the benzoyl group adopt a cis–trans conformation, respectively, with respect to the thiono S atom across the C—N bonds. The phenyl ring is twisted relative to the the thiourea mean plane, forming a dihedral angle of 24.16 (9)°. An intramolecular N—H...O hydrogen bond occurs. The crystal packing is stabilized by intermolecular N—H...O and C—H...O hydrogen bonds, forming a chain along the a axis.